2018
DOI: 10.3926/ic.1222
|View full text |Cite
|
Sign up to set email alerts
|

Clustering the mediators between the sales control systems and the sales performance using the AMO model: A narrative systematic literature review

Abstract: Purpose: To identify all types of sales force control systems in the academic literature, and to cluster the mediators between these controls and the performances, according to the AMO model (abilities, motivations, and opportunities), analysing how each of these three groups of mediators are influenced by control systems, and how they impact on the sales performance, using a systematic literature review.Design/methodology: Scientific papers published during the last 32 years, using as databases: Business Sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 111 publications
0
14
0
4
Order By: Relevance
“…• If the Confirmatory Composite Analysis approach (Henseler, 2017a;Schuberth et al, 2018a) is compatible with recent proposals made about the Confirmatory Tetrad Analysis (CTA) (Gudergan, Ringle, Wende & Will, 2008;Tabet, Lambie, G.W., Jahani, S., & Rasoolimanesh, 2019a. This would allow us to analyse the measurement models of the operational definitions of latent variables; e.g., the skills of a job post that a worker masters, Total Production Maintenance (TPM) (Kareem & Amin, 2017;Marin-Garcia & Mateo-Martínez, 2013;Reyes, Alvarez, Martinez & Guaman, 2018), Lean Manufacturing, or the AMO model (Benet-Zepf, Marin-Garcia & Küster, 2018;Marin-Garcia & Martinez-Tomas, 2016). This would allow us to discern if they are "cultural" dimensions and if they exist themselves (and can, thus, explain organisational performances in the same way as personality exists and explains people's conducts).…”
Section: Discussionmentioning
confidence: 98%
“…• If the Confirmatory Composite Analysis approach (Henseler, 2017a;Schuberth et al, 2018a) is compatible with recent proposals made about the Confirmatory Tetrad Analysis (CTA) (Gudergan, Ringle, Wende & Will, 2008;Tabet, Lambie, G.W., Jahani, S., & Rasoolimanesh, 2019a. This would allow us to analyse the measurement models of the operational definitions of latent variables; e.g., the skills of a job post that a worker masters, Total Production Maintenance (TPM) (Kareem & Amin, 2017;Marin-Garcia & Mateo-Martínez, 2013;Reyes, Alvarez, Martinez & Guaman, 2018), Lean Manufacturing, or the AMO model (Benet-Zepf, Marin-Garcia & Küster, 2018;Marin-Garcia & Martinez-Tomas, 2016). This would allow us to discern if they are "cultural" dimensions and if they exist themselves (and can, thus, explain organisational performances in the same way as personality exists and explains people's conducts).…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the techniques used by Benet-Zepf et al (2018) and Marin-Garcia and Martinez-Tomas (2016), the literature review methodology used in this paper uses a streamlined and systematic process as shown in Figure 1. The search started with the keyword search and then examining the literature for their relevance in industrial disaster.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale underlying the ability of sales outcome controls to enhance autonomous motivation is that sales outcome controls generally entail little monitoring. Management’s role is “hands-off,” allowing the correlation between compensation and sales results to serve as an evaluation system (Benet-Zepf et al , 2018).…”
Section: Hypotheses Developmentmentioning
confidence: 99%